Changing geography of the creative economy in Hungary at the beginning of the 21st century - Egedy, Tamás; Kovács, Zoltán; Szabó, Balázs (Hungarian Geographical Bulletin, 2018)
The Hungarian economy has gone through rapid transformation and modernization since the political changes of 1989/90. One of the signs of successful economic restructuring and re-integration to the world economywas the growing role of creative economy. In the present paper we analyse the changing geographical pattern of creative economy in Hungary, based on longitudinal statistical data. Our findings suggest growingcore-periphery relations in the spatial pattern of creative economy, especially cince the recent financial crisis. The relative weight of Budapest and its urban region has been continuously growing and even major regional centres are unable to keep pace with the Hungarian capital. We also found that cities in the Hungarian urban system became highly differentiated according to their attractiveness for creative firms and labour, and there is a growing competition among secondary cities for knowledge based and creative activities. The growing geographical concentration of the creative economy (especially the knowledge intensive industries) is partly the result of previous neoliberal regional and urban policies.